2021
DOI: 10.3390/toxins13050364
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Evolution of Resistance to Vip3Aa Insecticidal Protein in Mythimna separata (Walker) Is Not Related to Altered Binding to Midgut Receptors

Abstract: Laboratory selection for resistance of field populations is a well-known and useful tool to understand the potential of insect populations to evolve resistance to insecticides. It provides us with estimates of the frequency of resistance alleles and allows us to study the mechanisms by which insects developed resistance to shed light on the mode of action and optimize resistance management strategies. Here, a field population of Mythimna separata was subjected to laboratory selection with either Vip3Aa, Cry1Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
2
8
1
Order By: Relevance
“…As far as we know, this is the first study reporting detailed results from bioassays evaluating responses to Vip3Aa by field populations or laboratory strains of pink bollworm. Consistent with predictions based on the lack of shared midgut receptors between Vip and Cry toxins [14][15][16][17][18][19][20][21] and previous results from other lepidopterans, [22][23][24][25][26][27][28][29][30][31][32] the results here show strong crossresistance to Vip3Aa did not occur in strains of pink bollworm selected in the laboratory for > 700-fold resistance to Cry1Ac or to both Cry1Ac and Cry2Ab. Although the LC 50 of Vip3Aa was 3.5-fold lower for the Cry1Ac-resistant strain AZP-R than the Cry-susceptible laboratory strain APHIS-S, this does not provide clear evidence of negative cross-resistance because these strains are unrelated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As far as we know, this is the first study reporting detailed results from bioassays evaluating responses to Vip3Aa by field populations or laboratory strains of pink bollworm. Consistent with predictions based on the lack of shared midgut receptors between Vip and Cry toxins [14][15][16][17][18][19][20][21] and previous results from other lepidopterans, [22][23][24][25][26][27][28][29][30][31][32] the results here show strong crossresistance to Vip3Aa did not occur in strains of pink bollworm selected in the laboratory for > 700-fold resistance to Cry1Ac or to both Cry1Ac and Cry2Ab. Although the LC 50 of Vip3Aa was 3.5-fold lower for the Cry1Ac-resistant strain AZP-R than the Cry-susceptible laboratory strain APHIS-S, this does not provide clear evidence of negative cross-resistance because these strains are unrelated.…”
Section: Discussionsupporting
confidence: 92%
“…Both Vip3 and Cry toxins must bind specifically to midgut receptors to kill insects, 12,13 but strong cross‐resistance between them is not expected because they do not share midgut receptors 14–21 . Confirming this expectation, analysis of 48 pairwise comparisons between related strains of eight lepidopteran species found cross‐resistance was weak between Cry1 and Vip3 toxins and did not occur between Cry2 and Vip3 toxins 22 (also see the literature 23–32 ).…”
Section: Introductionmentioning
confidence: 91%
“…Finally, the mechanisms associated with Vip3A resistance will also need to be described. Recent data suggest that the mechanisms of insect resistance to Vip3A proteins are different from those described in insects that have evolved resistance to Cry proteins: it was reported that in some insects, such as Mythimna separata , the resistance to Vip3Aa is not related to altered binding to microvilli membranes ( 90 ). Furthermore, reduced expression of ALP in a Vip3-resistant strain of Heliothis virescens did not affect the binding of Vip3Aa to the microvilli membrane ( 91 ).…”
Section: Final Conclusionmentioning
confidence: 99%
“…The resistance mechanisms of M. separata to Vip3Aa may be account for this result. Quan et al [34] reported that the resistance to Vip3Aa is not related to altered binding to midgut receptors, while altered binding to membrane receptors was the main mechanism of resistance to Cry proteins. Polygenic resistance against Cry1, Cry2 and Vip3Aa protein has also been reported in a number of insect species [25,35,36].…”
Section: Discussionmentioning
confidence: 99%